Docência na educação superior: concepções de professores que ensinam Matemática: 2014 à 2018 - Arantes, Margareth Gomes Rosa (2018)
This research investigated the reality of the Mathematics teachers, their professional qualification, their teacher knowledge and the teaching-learning process of higher education, with the purpose of studying, analyzing, systematize and describe the conceptions about the teaching and learning that guide the thought and the practice of the mathematics teachers of the higher education. The trajectory coursed in this thesis has a quantitative character giving support to a qualitative analysis, leaving affirmed the solidity of the research. It was used questionnaires applied to 21 contributing teachers of 05 institutions of the south region of Goias, highlighting three categories: Professional Formation, Teachers knowledge and Conceptions of the Teaching and Learning Process. With the obtained data it was realized a statistical analysis to demonstrate the results and, to elucidate them, was based on the authors Bassanezi (2011), Demo (2004), Fiorentini (1995), Gatti (2007), Malusá (2003), Masetto (2012), Oliveira (2009), Saviani (2010), Severino (2008), Tardif (2014), Zabalza (2004), among others. The results revealed that the subjects researched value the professional formation and its knowledge, the disciplinary knowledge, the curricular knowledge and the experiential knowledge. In the process of teaching and learning the researched teachers are hesitant to conceive of new situations by remaining comfortable in teaching and demonstrate difficulty in perceiving the student as “Humans Beings” and create new methodologies focused in the learning of this student. Finally, this these suggests a methodological alternative which demonstrates a new possibility to teach in the higher education – Mathematical Modeling which establish a critical relation in the teachers professional qualification and their knowledge and a new and creative way aimed at students learning.